Unbelivable Boring Bart - Patterson, James (Jimmy patterson/ Little Brown and Company, 2018)
Invisible creatures are attacking the school, and a 12-year-old boy is the only one who can stop them in this fun, hilarious middle grade novel. Okay, so maybe Bartholomew Bean is only a hero in the video game app he created. But if he reveals his identity as the genius behind the game, he'll become the most popular kid in school! Or he could secretly use the game to get back at his bullies.